PERAN PARIWISATA RELIGI DAN BUDAYA DALAM PERMINTAAN WISATA CIREBON - Dananjaya, Ahmad Ghazy (UHN IGB Sugriwa Denpasar, 2025)
Cirebon, as a region rich in cultural and religious heritage, holds great potential as a prime tourist destination. This study aims to identify the role of religious and cultural tourism in boosting travel demand in Cirebon. Utilizing visitor data analysis and online news discourse through Structural Topic Modeling (STM) and SARIMAX methods, the research explores the relationship between media coverage, promotional strategies, and tourism trends. Findings reveal that cultural events such as the Muludan Festival and religious pilgrimages to Sunan Gunung Jati's tomb are key attractions. Digital promotions through social media and the involvement of human and virtual influencers enhance Cirebon's exposure as a travel destination. However, sustainability challenges, including overtourism and waste management, must be addressed to maintain tourist experience quality. This study provides strategic recommendations, including data-driven and technological management, to foster sustainable tourism development in Cirebon.